Diagnostic value of serum LDH in children with refractory Mycoplasma pneumoniae pneumoniae: A systematic review and meta-analysis - Wang, Shumin; Jiang, Zhiyan; Li, Xuejun; Sun, Chenghui; Zhang, Yixing; Xiao, Zhen (Frontiers in Pediatrics, 2023)
Background: To investigate the relationship between serum Lactate dehydrogenase (LDH) and refractory Mycoplasma pneumoniae pneumonia (RMPP) in juvenile individuals. Methods: Search Chinese databases and English databases. The retrieval time limit is from the establishment of the database to 2022-04-27. And screening and inclusion of relevant diagnostic test literature. The QUADAS-2 method was used to evaluate the quality of the included literature. The random effects model was used to combine sensitivity, specificity, likelihood ratio, diagnostic odds ratio, summary receiver operating characteristic curve, and area under summary receiver operating characteristic curve to evaluate the prediction value of LDH for RMPP. Subgroup analysis was used to explore the source of heterogeneity. Results: ① A total of 29 literatures that met the criteria were included in the study, and the quality of the literature was medium and high, with a total of 702,2 patients. ② The combined sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio, and area under the curve of the studies were: 0.75 (95% CI = 0.73-0.76), 0.73 (95% CI = 0.72-0.74), 3.61 (95% CI = 2.86-4.56), 0.30 (95% CI = 0.23-0.39), 13.04 (95% CI = 8.24-20.63), and 0.85(95% CI = 0.82-0.88). ③ The results of subgroup analysis showed that Compared with the subgroup with LDH threshold ≤400IU/L, the AUC increased from 0.84 (95% CI = 0.80-0.87) to 0.89 (95% CI = 0.86-0.91). Conclusions: The serum LDH has good accuracy for the diagnosis of RMPP and can serve as a diagnostic marker for RMPP.